2017
DOI: 10.2147/hiv.s126309
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual care may impact mental health and medication adherence in HIV+ populations

Abstract: ObjectiveTo explore a potential role for spirituality in medication-related needs assessment for integrated care in chronically ill populations.MethodA systematic literature review was conducted to explore the impact of faith beliefs on health and/or medication adherence in individuals with depression and/or HIV+/AIDS. Retrospective electronic medical record review of adult HIV+ patients of an urban primary care clinic with integrated mental health services was conducted, with Substance Abuse and Mental Illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 56 publications
2
40
0
4
Order By: Relevance
“…Of note, virtually all HIV‐infected caregivers in this study were already stably connected to HIV care and routine monitoring for HIV and general health. Given these critical preconditions, child QOL and psychosocial indices being comparable for HIV affected and unaffected caregivers may partly reflect a tangible benefit of HAART, access to routine health monitoring and possibly additional HIV‐related support services – for example, spiritual care , mental health counselling and nutritional supplementation that may be more common for HIV‐infected compared to HIV‐uninfected caregivers. Specific studies in the African setting – preferably prospective in design with larger sample size, are needed to clarify these findings including the suggestive evidence of caregiver HIV‐positive status‐associated deficits in QOL and positive outlook observed only among community control children.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, virtually all HIV‐infected caregivers in this study were already stably connected to HIV care and routine monitoring for HIV and general health. Given these critical preconditions, child QOL and psychosocial indices being comparable for HIV affected and unaffected caregivers may partly reflect a tangible benefit of HAART, access to routine health monitoring and possibly additional HIV‐related support services – for example, spiritual care , mental health counselling and nutritional supplementation that may be more common for HIV‐infected compared to HIV‐uninfected caregivers. Specific studies in the African setting – preferably prospective in design with larger sample size, are needed to clarify these findings including the suggestive evidence of caregiver HIV‐positive status‐associated deficits in QOL and positive outlook observed only among community control children.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Oji et al (2017) mentioned the term faith on several occasions but did not reveal any religious affiliations.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of HIV, it was suggested that an increase in religiosity/spirituality could improve the viral load and the level of CD4 cells (Aronson et al, 2006). Religion was often used as a coping mechanism and was linked to a higher social support, a lower rate of depression and PTSD, and an increased adherence to treatment in the case of HIV (Oji et al, 2017). Cancer patients with higher religiosity/spirituality experienced peace and felt safer emotionally (Jim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that approximately 90% of Iranians (USA 84%) report a religious affiliation, and 96% of Iranians (USA 82%) report religion as at least somewhat or very important in their lives (Hajiesmaeili et al 2016;The Pew Research Center 2008). Several systematic reviews of the literature support a relationship between religiosity promoting improved health behaviors (Oji et al 2017;Saad and Medeiros 2017) and lower all-cause mortality (Hatah et al 2015;McCullough et al 2000;Powell et al 2003;Saad and Medeiros 2017). Emerging evidence suggests that R/S are correlated with improved mental and physical health outcomes, including decreased rates of depression (Bonelli et al 2012;El-Hady and Kandeel 2017;Frih et al 2017;Kazemi and Baharami 2014;Saisunantararom et al 2015), anxiety, post-traumatic stress disorder, suicide, and coronary heart disease (Bashar et al 2018).…”
Section: Religiosity and Spiritualitymentioning
confidence: 99%